Analisis Kebermanfaatan Dan Kemudahan Wajib Pajak Pada Dosen Tetap Universitas Tribhuwana Tunggadewi Malang Dalam Penggunaan e-filling Sebagai Sistem Pelaporan SPT Tahunan Secara Elektronik - Risnaningsih Risnaningsih; Hendrik Suhendri; Lutfiyanto Lutfiyanto (Universitas Katolik Soegijapranata, Semarang, 2022)
The purpose of this study was to find out how taxpayers respond to the usefulness and convenience of e-filling as an annual tax return reporting system. The object of this research is a permanent lecturer at Tribhuwana Tunggadewi University. The method used in this research is descriptive qualitative. The sampling technique used the Slovin formula and obtained 36 respondents. Collecting data in this study through questionnaires and interviews. The data analysis used in this study used descriptive analysis using percentages. The results show that for the usefulness of e-filling, e-filling is categorized as very useful with a percentage of 88% and for ease of e-filling, e-filling is also categorized as easy with a percentage of 84%. Which is corroborated by the interview results.